Pengumpulan Data Base Sumber Antioksidan Alami Alternatif Berbasis Pangan Lokal di Indonesia - Silvia, Deli; Katharina, Kezia; Hartono, Stefanny Agness; Anastasia, Vanessa; Susanto, Yunita (Surya Octagon Interdisciplinary Journal of Science and Technology, 2016)
Nowadays the interest in food with antioxidant content continues to increase, especially the natural antioxidant content found in the local Indonesian food. Therefore, the aim of this research is to explain some kind of natural antioxidant compounds commonly found in food, describe several methods of extraction and food processing, and gathering data about the local food products that could be an alternative natural source of antioxidants. The research method used is literature study by analyzing data based on references and journals that already exist. From this study, the result showed that antioxidant compounds in food products commonly found in the form of Vitamin C, Vitamin E, beta carotene, selenium, superoxide dismutase (SOD), and flavonoid. Some local food that can be an alternative source of antioxidants found in vegetables, fruits, spices, as well as animal products that are easily found around the community. Extraction methods commonly used to identify the antioxidant compounds are solvent extraction and mechanical extraction.